SINTESIS TURUNAN ASETOFENON DARI 1-(4-ASETOKSIFENIL-3-METOKSI)-2-PROPANIL FORMAT - Kusmiyati Kusmiyati; Sabirin Matsjeh; Jumina Jumina (Universitas Ahmad Dahlan, 2012)
The Synthesis of acetophenone derivative from 1-(4-acetoxyphenyl-3-methoxy)-2-propanyl formate through Fries Rearrangement in order to produceortho hidroxy acetophenone derivative as starting material of Flavanoid compound hasbeen done. The reaction of 1-(4-acetoxyphenyl-3-methoxy)-2-propanyl formate wasdone by heating at 120 Â°C for 3 hours under AlCl3, dichloromethane as the catalyst andsolvent, respectively. The structure of the compound was identified using Infra Redspectrometry (IR) dan GC-MS. Fries rearrangement of 1-(4-acetoxyphenil-3-methoxy)-2-propanyl formate produce 1-(2-hyidroxy-3-methoxy-5-propenyl)-acetophenone and 1-(2-hyidroxy-3-methoxy-5-propanyl)-acetophenone as sideproduct with product rendemen were 43.26% and 9.48%, respectively.